The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5535/arm.2014.38.6.742
|View full text |Cite
|
Sign up to set email alerts
|

Korean Version of the Scale for the Assessment and Rating of Ataxia in Ataxic Stroke Patients

Abstract: ObjectiveTo investigate the intra-rater and inter-rater reliability and usefulness of the Korean version of the Scale for the Assessment and Rating of Ataxia (K-SARA) in ataxic stroke patients.MethodsThe original SARA was translated into Korean, back translated to English, and compared to the original version. Stroke patients (n=60) with ataxia were evaluated using the K-SARA by one physiatrist and one occupational therapist. All subjects were rated twice. We divided the subjects into 5 groups by Functional Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
8
0
4
Order By: Relevance
“…The SARA is used to assess the severity and treatment effectiveness of cerebellar ataxia. Some studies have shown its usefulness in stroke individuals [ 25 , 26 ]. The total score ranges from 0 (no ataxia) to 40 (severe ataxia), and it is composed of the following 8 items [ 27 ]: 1 gait (0–8); 2 stance (0–6); 3 sitting (0–4); 4 speech disturbance (0–6); 5 finger chase (0–4); 6 nose finger test (0–4); 7 fast alternating hand movement (0–4); and 8 heel-shin slide (0–4); the four extremities are evaluated bilaterally, and the mean values are used to calculate the total score [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The SARA is used to assess the severity and treatment effectiveness of cerebellar ataxia. Some studies have shown its usefulness in stroke individuals [ 25 , 26 ]. The total score ranges from 0 (no ataxia) to 40 (severe ataxia), and it is composed of the following 8 items [ 27 ]: 1 gait (0–8); 2 stance (0–6); 3 sitting (0–4); 4 speech disturbance (0–6); 5 finger chase (0–4); 6 nose finger test (0–4); 7 fast alternating hand movement (0–4); and 8 heel-shin slide (0–4); the four extremities are evaluated bilaterally, and the mean values are used to calculate the total score [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…En este tipo de Examinación aún existen discordancias con respecto a la forma de evaluación clínica, en cuanto a población adulta se reporta el uso de la escala MRC ( Medical research council) como una escala manual de fuerza (Paternostro-Sluga, 2008). Por el contrario, en población pediátrica se reporta el uso de Dinamometría manual, escala MRC, Daniels and Worthingham test, manual muscle test (MMT), estos test son aplicados en niños con patologías neuromusculares como espina bífida, distrofias musculares y parálisis cerebral (Defrasne Ait-Said, 2007) (Jain, 2006) (Lee-Valkov, 2003) (Mahony, 2009) (Nunes, 2016) (Tan, 2016) Marcha y locomoción En adultos, se reporta el uso de tecnología a través de plataforma de presión y fuerza las cuales permiten identificar anormalidades durante el patrón de marcha en factores cinéticos y cinemáticos (Condron, 2002) (Deschamps K. S., 2016) (Deschamps, 2015) (Wafai, 2015), además de eso se reporta el uso de las pruebas clínicas de la caminata de 10 metros la cual puede identificar anormalidad en la velocidad de la marcha (Amatachaya, 2014) (Peters, 2013) (Scivoletto, 2011) y el test Scale for the assessment and rating of Ataxia (SARA) el cual identifica perturbaciones en la marcha que afectan la realización de actividades de la vida diaria (Braga-Neto, 2010) (Kim, 2014) (Schwabova, 2014) (Tan S. N., 2013). Por el contrario, en pediatría se reporta el uso de la escala Pediatric Reach Test en la identificación de alteraciones de la estabilidad (Bartlett, 2003) (Rajendran, 2012).…”
Section: Desempeño Muscularunclassified
“…Modified from Lauterbach et al 3) PLC: pathological laughing and crying. Modified from Kim et al 10) Table Ⅲ…”
Section: Proposed Plc Criteriamentioning
confidence: 99%